The joint associations of pulmonary function and relative grip strength with metabolic syndrome in lung-healthy older adults: Cross-sectional findings from the Physical Activity and Aging Study - Joey M. Saavedra; Elizabeth C. Lefferts; Brian Downer; Duck-chul Lee (PLOS Aging and Health, 2026)
While lung disease is strongly associated with metabolic syndrome (MetS), the relationship between healthy pulmonary function and metabolic syndrome (MetS) in older adults remains unclear. It is also unknown if this association is independent of relative grip strength, a robust correlate of MetS. We examined the association between Z-score categories of the Forced Expiratory Volume in 1 second (FEV1) and prevalent MetS in a cohort of lung-healthy older adults. This cross-sectional study analyzed data from an ongoing cohort of older adults living in the US Midwest. Pulmonary function was assessed by spirometry, grip strength was assessed by handgrip dynamometry and then divided by body weight (relative grip strength), while MetS was defined using consensus criteria. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of MetS across tertiles of pulmonary function and relative grip strength. Four exposure groups were created to evaluate joint associations, with the theoretically healthiest group (“high pulmonary function, high relative grip strength”) serving as the reference. Among 353 participants (65–95 years, 63% female), 115 (32.6%) had MetS. A significant linear trend between tertiles of FEV1 and MetS was observed in minimally adjusted models (P < 0.05), but this trend was attenuated after adjustment for relative grip strength. Conversely, relative grip strength showed a significant linear trend with MetS across all models, even when adjusting for FEV1 (P < 0.001). In the joint analysis, the ORs (95% CIs) of MetS were 1.13 (0.56–2.26), 3.27 (1.70–6.27) and 4.50 (2.20–9.22) for the “low pulmonary function, high relative grip strength,” “high pulmonary function, low relative grip strength,” and “low pulmonary function, low relative grip strength” groups, respectively . Thus, low pulmonary function may represent a phenotype with higher odds of MetS, but this association is not independent of relative grip strength.